The road to Christmas - Roberts, Sheila, 1951- (Mira, 2022)
Michelle and Max are not planning on a happy holiday. Their marriage is in shambles and the D word has entered their vocabulary. But now their youngest daughter, Julia, wants everyone to come to her new house in Idaho for Christmas, and she's got the guest room all ready for Mom and Dad. Oh, joy. Their other daughters, Audrey and Shyla, are driving up from California and hoping to meet a sexy rancher for Audrey along the way. What they don't plan on is getting stranded on a ranch when the car breaks down. The ones with the shortest drive are Grandma and Grandpa, also known as Hazel and Warren. It's still a bit of a trek, and Hazel doesn't like the idea of driving all that way in snow, but Warren knows they'll have no problem. They have a reliable car, and snow tires and chains if they need them. They'll be fine. Surprises lie in store for all three sets of intrepid travelers as they set out on three very different adventures, all leading to one memorable family Christmas.